Criteria and diagnostic scale of the post-combat delayed response (tension) syndrome - Danilevska, N.; Данілевська, Наталя Володимирівна (My University, 2024)
Objective. War participation risks mental disorders. Ukrainian combatants in Anti-Terrorist Operation/Joint Forces Operation since 2014 receive psychiatric care. Some show unique symptoms, not fitting recognized disorders, termed post-combat delayed response (tension) syndrome. The aim of this study was to establish diagnostic criteria and develop a scale of differential diagnosis of post-combat delayed response (tension) syndrome. Methods. This was a clinical retrospective study conducted on the basis of Zaporizhzhia Military Hospital and Zaporizhzhia and State Medical University, Ukraine, in the period from 2015 to 2021. Combatants of Ukraine—members of Anti-Terrorist Operation/Joint Forces Operation were involved in the study. In total, 426 male combatants were surveyed from whom those suffering from post-traumatic stress disorder (n = 24), neurasthenia (n = 35), and postcombat delayed response (tension) syndrome (n = 46) were selected. Results. The key symptoms of post-combat delayed response (tension) syndrome were selected and ranked in order of their differential diagnostic value. The diagnostic scale for post-combat delayed response (tension) syndrome was developed, which consists of 12 points. Conclusions. The received anamnestic information is important for classifying patients at risk of post-combat delayed response (tension) syndrome.
Keywords: combat trauma; post-combat stress reaction; health disorders; combatants